2016
DOI: 10.1021/acsami.6b11610
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxy of Fe3O4/Muscovite: A New Perspective for Flexible Spintronics

Abstract: Spintronics has captured a lot of attention since it was proposed. It has been triggering numerous research groups to make their efforts on pursuing spin-related electronic devices. Recently, flexible and wearable devices are in a high demand due to their outstanding potential in practical applications. In order to introduce spintronics into the realm of flexible devices, we demonstrate that it is feasible to grow epitaxial FeO film, a promising candidate for realizing spintronic devices based on tunneling mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
72
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 26 publications
2
72
2
Order By: Relevance
“…Hence, flexible epitaxial thin film is an essential component of wearable sensors . Recently, some flexible ferromagnetism, ferroelectricity, conductivity, and ME coupling epitaxial thin films have been successfully obtained by using flexible substrate (Mica) or transfer method (peel epitaxial thin films from their hard substrates), such as ITO/Mica, Fe 3 O 4 /Mica, BiFeO 3 ‐CoFe 2 O 4 /Mica, PZT/Mica, BaTi 0.95 Co 0.05 O 3 /Mica, LiFe 5 O 8 , and CoFe 2 O 4 etc . However, the flexible microwave magnetism epitaxial thin films are still scarce up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, flexible epitaxial thin film is an essential component of wearable sensors . Recently, some flexible ferromagnetism, ferroelectricity, conductivity, and ME coupling epitaxial thin films have been successfully obtained by using flexible substrate (Mica) or transfer method (peel epitaxial thin films from their hard substrates), such as ITO/Mica, Fe 3 O 4 /Mica, BiFeO 3 ‐CoFe 2 O 4 /Mica, PZT/Mica, BaTi 0.95 Co 0.05 O 3 /Mica, LiFe 5 O 8 , and CoFe 2 O 4 etc . However, the flexible microwave magnetism epitaxial thin films are still scarce up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study has shown the growth of epitaxial Fe 3 O 4 on muscovite to advance the field of spintronics, because Fe 3 O 4 is the most attractive material for such applications due to its high Curie temperature (858 K) and predicted nearly 100% spin polarization. 38 The verification of the cyclability and endurability of Fe 3 O 4 / muscovite heterostructure opens a new pathway towards flexible spintronics. Lately, there is a demonstration of the heteroepitaxy with Pb(Zr,Ti)O 3 , a classic ferroelectric material, on muscovite.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is no misorientation control of vdW oxide heteroepitaxy, implying an Fig. 2 A summary on the current status of vdW oxide heteroepitaxy 31,34,[36][37][38][39][40] Van der Waals oxide heteroepitaxy Y-H Chu important research direction since the anisotropic property is a key feature in most epitaxial thin film system. (4).…”
Section: Introductionmentioning
confidence: 99%
“…Among the flexible electronic devices, those with multifunctional properties, especially with magnetic properties, receive particular attentions in biomedical giant magnetoresistance sensors, magnetoelectric devices, energy harvesting devices, microactuators, microwave devices, etc. With respect to the stability, fabrication compatibility, and controllability, intense explorations have been made on magnetic oxide materials, such as Fe 3 O 4 , La 0.7 Sr 0.3 MnO 3 , spinel ferrite, etc. Among them, spinel ferrite LiFe 5 O 8 (LFO) is one of the most attractive materials due to its excellent magnetic and dielectric properties.…”
mentioning
confidence: 99%
“…As shown in Figure e,f, H c and M s slightly increase with increasing 1/ r , while M r keeps unchanged under different bending status. The slight increment of M s can be explained by the magentoelastic energy density equationsEε=1/2μ0HeffMnormalscos2θ=3/2λnormalsYεnormalmcos2θwhere H eff is the strain‐induced in‐plane effective magnetic anisotropy field, θ is the angle between the in‐plane magnetization and strain (in our case, θ = 0), λ s and Y are the saturation magnetostriction and Young's modulus along the [100] direction, respectively. Here λ s = −27.8 ppm, Y ≈ 1.74 × 10 12 dyne cm −1 .…”
mentioning
confidence: 99%